Biological and chemical products for the control of gray and acid rot in the cultivation of vines (vitis vinifera l.) under field conditions, Chongoyape 2015 - Rivera Puelles, Thalía Puelles (2016)
The objective of the present investigation was to determine that biological and chemical products allow control of gray rot and acid rot of vitis vinifera L. under field conditions, carried out in Chongoyape district, 2015. It was used the design of complete random blocks with 5 treatments and four replicates with 60 clusters per treatment. The results obtained showed that there was no presence of Botrytes cinerea causal agent of "Gray Pudding" in both laboratory and field tests, but the complex of microorganisms that caused "Acid Pudding" was found, among which the bacteria Acetobacter Spp, yeast like Kloeckera spp and fungi like Aspergillus niger.